Effects of drying conditions on physical, chemical and biological properties of betel (piper betle L.) leaves powders and its application in lemongrass-scented betel tea - Mazaitul Akma Suhaimi
Fresh betel (Piper belle L.) leaves are highly perishable due to high moisture content (>80%), hence possess challenges in commercialisation. Dried betel leaves allow it to be utilized as functional food ingredients. However, the drying process on the leaves might cause degradation of some valuable phytochemicals is yet to be discovered. Furthermore, findings regarding betel herbal tea were rarely reported. This study aimed to examine the proximate compositions, physicochemical properties, biological activities and functional characteristics of betel leaves powder dried at different drying conditions; optimise the steeping conditions of lemongrass-scented betel tea; and evaluate the proximate compositions, physicochemical properties, biological activities, and sensory attributes of lemongrass-scented betel tea. Betel leaves were dried using freeze-drying (FD) and hot air-drying (HAD) at 40, 50 and 60°C (HAD- 40, HAD-50, and HAD-60, respectively) methods. The betel leaves powders were assessed for proximate compositions and physicochemical properties using a standard method while antidiabetic properties and functional characteristics were determined using the alpha-glucosidase inhibition activity and centrifuging methods, respectively. Betel leaves powder was substituted with lemongrass stalk powder in proportions of 5, 15 and 25% to prepare infusion LBT-5, LBT-15, and LBT-25, respectively. An infusion prepared without lemongrass served as a control (LBT -0). The optimum steeping conditions for all of the lemongrass-scented betel tea preparation were determined and analysed for proximate compositions, physical properties, antidiabetic properties, and antimicrobial activity. All lemongrass-scented betel tea was evaluated for sensory characteristics by a 7 -hedonic scale. FD preserved most nutrients of betel leaves powder but demonstrated the lowest bulk density value. FD also retained most colour, had the highest pH, total titratable acidity, 1,I-diphenyl-2-picrylhydrazyl (DPPH) fr r i 1- a nging ability, and water holding capacity values but lowest values for water activity, oil holding capacity and ICso value of a-glucosidase inhibition activity of betel leaves powder. HAD-40 showed the highest values for total phenolic content (TPC), total flavonoids content (TFC), and ferric reducing antioxidant potential (FRAP). For lemongrass-scented betel tea preparation, the first steeping and 10 min steeping time showed the highest values for TPC, TFC, DPPH, and FRAP. LBT-O demonstrated the biggest inhibition zone, and the lowest minimum inhibitory concentration and minimum bactericidal concentration values. However, the a-glucosidase inhibition activity of LBT -25 was the high . L -25 received the highest score for overall acceptability. Different drying conditions infTuemm ilie content of proximate, physicochemical properties, biological activities and functional characteristics of betel leaves powder. The suitable processing method in the production of betel leaves powder can be identified for further applications as food ingredients, depending on the required end product characteristics and quality. The findings indicate that betel leaves powder has the potentials to be utilised as a functional food ingredient. The practical results could be transferred to an interested industry partner for the commercialisation of lemongrass-scented betel tea.